The impact of COVID-19 pandemic on mortality among adults receiving care for chronic health conditions in rural South Africa: findings from Agincourt health and socio-demographic surveillance system - Daniel Ohene-Kwofie; Cyril Chironda; Jean Bashingwa; Tshegofatso Seabi; Audry Dube; Beth Tippett-Barr; Francesc Xavier Gómez-Olivé; Kathleen Kahn; Stephen Tollman; Chodziwadziwa W. Kabudula (Population Health Metrics, 2025)
Abstract Background Globally, the COVID-19 pandemic greatly interrupted healthcare programmes, and resulted in excess deaths. The age-specific mortality profile of the COVID-19 disease indicates that older people and those with comorbidities, specifically diabetes and hypertension, face a higher risk of mortality. In South Africa, excess deaths from natural causes in 2020 and 2021 were estimated to be nearly three times higher than the reported COVID-19 deaths. The study aims to characterise and compare mortality changes over the period 2015–2021 among individuals receiving care for HIV, hypertension and diabetes, in a rural South African setting. Methods Data from the Agincourt Health and Demographic Surveillance System and the Hospital-Clinic link system was used to characterise the sex and age-specific mortality patterns for HIV, hypertension, and diabetes for the period before (2015–2019) and during the COVID-19 pandemic (2020–2021). Cox regression model was used to investigate the risk factors associated with death before and during the COVID-19 period for individuals receiving care for these three major chronic conditions of interest in South Africa. Results Among individuals receiving care for chronic conditions in primary healthcare facilities there was a general increase across the years from 2015 to 2021; HIV from 23.3 to 48.8%; for hypertension from 31.1 to 46.1%; and for diabetes from 5.1 to 6.4%. Mortality rates, particularly among females, as well as individuals, aged 65+, increased from 2019 to 2021 (during the pandemic) reversing the progressive declining trend from 2016 to 2019. Mortality rate among persons with HIV, and diabetes or hypertension increased by up to 26% and 70%, respectively during the COVID-19 pandemic period, particularly among women. Differences were noted across individual and household factors, with age, sex, and education being associated with mortality risk for persons living with HIV, hypertension and/or diabetes. Conclusions This study shows increased mortality during the COVID-19 pandemic for individuals with chronic conditions in a rural South African setting, particularly among the elderly with hypertension, and diabetes, as well as those with comorbidity. The findings highlight the need to strengthen HIV, diabetes, and hypertension screening and care programmes to improve survival outcomes, especially in times of pandemics like COVID-19.